A preliminary study on the effect of the combination of Blaptica dubia (Order: Blattodea) and commercial fish feed on red hybrid tilapia, Oreochromis sp. (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Fish meal and soybean meal are the main sources of protein in most fish feeds. Changes in feed and fish production costs are a concern for aquaculturists. Because they are a natural component of fish diets and have a high protein, vitamin, and digestibility profile, insects may be able to contribute to meeting the growing demand for fishmeal. This study was a preliminary investigation on the effect of various dietary combinations (Blaptica dubia + commercial pellet) on the weight of red hybrid tilapia, Oreochromis sp. fry. The Oreochromis sp. fingerlings were acclimatized to the laboratory condition for seven days. Five different mixtures of feed were concocted [T1 (60% B. dubia + 40% commercial pellet), T2 (70% B. dubia + 30% commercial pellet), T3 (80% B. dubia + 20% commercial pellet), T4 (90% B. dubia + 10% commercial pellet) and T5 (100% B. dubia)]. The control group of Oreochromis sp. was fed with 100% commercial pellet. Throughout the experiment period, the growth of the fish was monitored weekly for 15 weeks. Then, the fish were euthanatized, and the liver was subjected to histology analysis. The results show that T3, T4, and T5 feed mixtures promote the best growth and survival rate for Oreochromis sp. while causing liver damage. T1 and T2 fish feed ratios are better alternatives as they promote healthy fish and increased weight (p < 0.05).
Keywords: protein source; fish feed; Oreochromis spp; Blaptica dubia; weight; histology